RURAL-URBAN DISPARITIES IN DETERMINANTS OF BCG IMMUNIZATION COVERAGE FOR CHILDREN AGED 0-3 MONTHS IN INDONESIA - Hidayatullah BW, Nur Mutiara Husnah; Astutik, Erni; Hargono, Arief (Jurnal Biometrika dan Kependudukan, 2025)
Bacillus Calmette–Guérin (BCG) immunization plays a crucial role in preventing tuberculosis, especially in developing countries like Indonesia. Its coverage is influenced by various factors that differ between urban and rural areas. This study aimed to identify factors associated with BCG immunization among infants aged 0–3 months in urban and rural Indonesia. This study used data from the 2017 Indonesia Demographic and Health Survey (IDHS), including 562 rural and 476 urban respondents. Variables analyzed included maternal age, education, household wealth, contraceptive use, and ANC visits. Chi-square tests and multiple logistic regression were conducted separately for urban and rural areas. The findings showed that 64.2% of urban and 48.7% of rural children received BCG immunization. In rural areas, children from the richest households were more likely to be immunized compared to those from the poorest households (OR = 2.29; 95%CI = 1.1–4.6). Children of mothers with higher education in urban areas were more likely to receive BCG compared to those with lower education (OR = 3.43; 95%CI = 1.3–9.0), as were those with secondary education (OR = 2.28; 95%CI = 1.1–4.4). Mothers who used contraception were also more likely to immunize their children compared to those who did not (OR = 2.71; 95%CI = 1.5–4.8). BCG coverage remains lower in rural communities. Improving coverage requires expanding access to health services in rural areas and strengthening education and contraceptive programs in urban settings.